2022
DOI: 10.1016/j.jpedsurg.2021.06.014
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the COVID-19 pandemic on presentation and severity of traumatic injury due to physical child abuse across US children's hospitals

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
19
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 27 publications
1
19
1
Order By: Relevance
“…This may not necessarily indicate that CM rates are decreasing, but that CM is being identified in other settings than the ED. Lastly, the findings did not indicate a significant increase in hospitalization following an ED visit for CM, which contradicts data from the across the US ( De Boer et al, 2022 ). It should be noted that in our data there were small cell sizes for inpatient admission resulting in low power and our inability to infer significance.…”
Section: Discussioncontrasting
confidence: 86%
“…This may not necessarily indicate that CM rates are decreasing, but that CM is being identified in other settings than the ED. Lastly, the findings did not indicate a significant increase in hospitalization following an ED visit for CM, which contradicts data from the across the US ( De Boer et al, 2022 ). It should be noted that in our data there were small cell sizes for inpatient admission resulting in low power and our inability to infer significance.…”
Section: Discussioncontrasting
confidence: 86%
“…Over the course of the COVID-19 pandemic, several centers have reported overall decreased trauma volumes, however with more severe injuries sustained 2 . This finding was unfortunately also observed with cases of child abuse: lower in volume, but higher in severity 4 . Cases of domestic violence have been observed to rise during the pandemic 5 .…”
Section: Introductionmentioning
confidence: 52%
“… 23 Several studies utilizing the Pediatric Health Information System found fewer NAT cases. 13 , 14 , 24 Another multicenter study from the Western Pediatric Surgery Research Consortium found no increases in NAT during the early months of the pandemic. 25 However, the COVID-19 pandemic affected each community differently, with varying state and city responses, social distancing guidelines and dates, local unemployment rates, etc.…”
Section: Discussionmentioning
confidence: 99%